2017
DOI: 10.1017/s0007114517002720
|View full text |Cite
|
Sign up to set email alerts
|

The dietary diversity and stunting prevalence in minority children under 3 years old: a cross-sectional study in forty-two counties of Western China

Abstract: As a key indicator of childhood malnutrition, few studies have focused on stunting in relation to various socio-economic factors in which disadvantaged groups face in China. We conducted a community-based cross-sectional study incorporating forty-two rural counties in seven western provinces of China in 2011. In total, 5196 children aged 6-23 months were included. We used Poisson regression to examine risk factors for inadequate minimum dietary diversity (MDD) and stunting status, respectively. Overall, the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
38
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 25 publications
11
38
0
5
Order By: Relevance
“…Facility delivery might allow for more chances to have appropriate and timely obstetric and medical care and to receive information about childcare (Pacagnella et al, ). Similar results were found in a cross‐sectional study in Western China (Wang et al, ) and in a study using the Bangladesh DHS (Hong, Banta, & Betancourt, ). In our study population, mothers who delivered at home also exhibited lower utilization of antenatal and post‐natal services than those with facility delivery (data not shown).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Facility delivery might allow for more chances to have appropriate and timely obstetric and medical care and to receive information about childcare (Pacagnella et al, ). Similar results were found in a cross‐sectional study in Western China (Wang et al, ) and in a study using the Bangladesh DHS (Hong, Banta, & Betancourt, ). In our study population, mothers who delivered at home also exhibited lower utilization of antenatal and post‐natal services than those with facility delivery (data not shown).…”
Section: Discussionsupporting
confidence: 87%
“…Facility delivery might allow for more chances to have appropriate and timely obstetric and medical care and to receive information about childcare (Pacagnella et al, 2014). Similar results were found in a cross-sectional study in Western China (Wang et al, 2017) and in a study using the Bangladesh DHS (Hong, Banta, & Betancourt, 2006).…”
Section: Delivery Locationsupporting
confidence: 68%
“…We investigated a range of gender‐related risk factors. Maternal education is a well‐established predictor of child feeding practices and nutritional status (Boyle et al, ; Wachs, Creed‐Kanashiro, Cueto, & Jacoby, ; Wang et al, ). A study conducted in Addis Ababa, Ethiopia, reported that mother's attainment of secondary education and above was associated with higher odds of achieving minimum dietary diversity among children 6–23 months old (Solomon, Aderaw, & Tegegne, ).…”
Section: Discussionmentioning
confidence: 99%
“…Karakteristik pada anak yang menyebabkan stunting cukup luas dalam 12 artikel yang di review, antara lain : bayi dengan berat lahir rendah dan kebanyakan bayi yang berjenis kelamin laki -laki (Aryastami et al, 2017;Oliviana, Deandra, &Hubaidiyah, 2016;Rachmi et al, 2016;Torlesse et al, 2016), bayi yang lahir premature (Boylan et al, 2017;Endy p, Prawirohartono, S, & Mohammad, 2016), tidak pernah mendapatkan ASI atau ASI yang diberikan tidak cukup selama 6 bulan (Aryastami et al, 2017;Huriah, 2017;Jiang et al, 2015;Rachmi et al, 2016;Wang et al, 2017).…”
Section: Alur Pencarian Artikel Hasilunclassified
“…6, No. 2, Desember 2019, 113-121 118 (Wang et al, 2017) DOAJ focused on stunting in relation to various socio economic factors in which disadvantaged groups face in China crosssectional survey China risk factors for inadequate minimum dietary diversity (MDD) and stunting status, respectively. Overall, the proportion of children not meeting MDD .…”
Section: Bruneimentioning
confidence: 99%